Recurrence/persistence of cervical intraepithelial neoplasia after undergoing a LEEP conization at Instituto Nacional de Enfermedades Neoplásicas - Venegas-Rodríguez, Gino (2017)
Objective: To determine the incidence of recurrence/persistence of cervical intraepithelial neoplasia (CIN) in patients who underwent a loop electrosurgical excision procedure (LEEP) at the Department of Gynecologic Oncology of Instituto Nacional de Enfermedades Neoplásicas (INEN). Materials and methods: A retrospective cohort study in which medical records of patients who underwent a LEEP conization from January 2002 to December 2003 were examined. After the LEEP conization, patients were divided into two groups: one with positive margin and another one with negative margin. Follow-up was performed every 3 months and consisted of a physical examination, Pap test and colposcopy. The outcome was recurrence of CIN. To assess the risk of CIN recurrence among the study groups, relative risk (RR) and its respective 95% confidence interval (CI) were calculated. Results: A total of 451 patients underwent a LEEP conization during the study period. The mean age was 35.32 years old, the mean number of sexual partners was 2.1 and the mean number of children was 2.7. One hundred and nine (109) patients (25%) showed a positive margin and 342 (75%) showed a negative one. Out of these subjects, only 94 and 102, respectively, met the eligibility criteria and were followed. The mean follow-up period was 21.74 months. The incidence of recurrence/persistence in patients with positive margin was 5.5%, while the incidence of recurrence/persistence in the group of patients with negative margin was 1.96%. We found no significant differences in the risk of CIN recurrence in the group of patients with positive margin versus patients with negative margin. RR = 2.7, 95% CI (0.41 to 33.8). Conclusion: There was no significant difference in the incidence of cervical intraepithelial neoplasia between patients with positive margin and patients with negative margin.